Pit slope monitoring and back analysis of the Berkeley pit - W. C. Goldberg; E. M. Frizzell (Society for Mining, Metallurgy & Exploration, 1989)
Monitoring slope displacement in open-pit mines can help predict collapses and prevent serious damage, injuries, and fatalities. Early detection of movement may indicate the need to modify slope geometry, initiate dewatering if the slope is wet, or consider artificial support measures such as cable bolting. Slope monitoring at the Berkeley pit was carried out with varying degrees of intensity and continuity for about 15 years. Some of the old mine records are still intact and accessible. Slope monitoring data can therefore be collected and published for the benefit of other mine operators. Because prediction of slope failures is empirical in nature, publication of several well documented case studies will be a valuable contribution to the industry. Background - Berkeley pit Open-pit mining of copper from the Berkeley pit, located on the east side of Butte, MT, began in 1955 and ceased in 1982. During that time, about 1 Gt (1.2 billion st) of material were removed to form a pit about 1.8 km wide by 2.1 km long (6000 ft by 7000 ft) at the rim, and 550 m (1800 ft) deep as measured from the high hill on the northwest side. From the south side, the pit only measures 365 m (1200 ft) deep. The Berkeley pit was first owned and operated by Anaconda Minerals Co., and subsequently by Arco. Following its closure in April 1982, the mine began to fill with water. Washington Construction purchased the property in 1986, and Montana Resources Inc. began mining to the east of the Berkeley pit in July 1986. Numerous instances of slope failure were recorded during the course of mining and several intensive geotechnical investigations were conducted in an effort to optimize the mine design. One of the last and most comprehensive studies was initiated in 1977. For purposes of geotechnical analysis, the mine was divided into nine design sectors on the basis of geologic conditions, geographic orientation, and economic importance (Fig. 1). Only two of these sectors - the concentrator and the southeast corner - are considered here. Material properties were obtained from several studies of samples collected from the mine and adjacent areas. The slope was monitored using standard surveying techniques to record the amount of movement in an area. The